A mechanochemical model for rho GTPase mediated cell polarization - Kopfer, Kai H.; Jäger, Willi; Matthäus, Franziska (Journal of theoretical biology, 2020)
Directed motility of eukaryotic cells requires the polarization of the actomyosin cytoskeleton. In many cell types the polar alignment of the actomyosin cytoskeleton occurs in response to a front-rear symmetry break of active Rho GTPase. Experimental evidence in neutrophils indicates that membrane tension plays an important role in the confinement of active Rac to the front domain. We suggest a mechanochemical model for polarization, including Rho GTPase mediated actomyosin cytoskeleton dynamics and changes in membrane tension as an upstream controller of Rho GTP that reflects this observation. The model comprises the Rho GTPases Rac and RhoA which can become activated in response to external signals. The active states regulate the actomyosin mechanics. The model cell is considered as a thin, effectively two dimensional, sheet adhering to a flat substrate. Morphological changes of the actomyosin cytoskeleton induce changes in membrane tension. We numerically show that the model exhibits key features of neutrophil polarization. The model accounts for a simple mechanochemical circuit with the ability to generate robust polarity patterns, wherein cell mechanics serve as a long range signal transmitter.